2018
DOI: 10.6061/clinics/2018/e309
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder and severe maternal morbidity: is there an association?

Abstract: OBJECTIVE:To evaluate the occurrence of Post-Traumatic Stress Disorder among women experiencing a severe maternal morbidity event and associated factors in comparison with those without maternal morbidity.METHODS:In a retrospective cohort study, 803 women with or without severe maternal morbidity were evaluated at 6 months to 5 years postpartum for the presence of Post-Traumatic Stress Disorder. Interviews were conducted by telephone and electronic data was stored. Data analysis was carried out by using χ2, Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 28 publications
1
37
0
3
Order By: Relevance
“…On the contrary, similar studies in Malaysia [10] and England [5] found no significant difference regarding the risk of depression among women with and without MNM. Similarly, there is contradicting evidence regarding the association between hospital admission due to pregnancy complications and post-traumatic stress disorder (PTSD) [5,6,11]. This study aims to investigate mental health (depression and PTSD) and QoL of these women over time.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the contrary, similar studies in Malaysia [10] and England [5] found no significant difference regarding the risk of depression among women with and without MNM. Similarly, there is contradicting evidence regarding the association between hospital admission due to pregnancy complications and post-traumatic stress disorder (PTSD) [5,6,11]. This study aims to investigate mental health (depression and PTSD) and QoL of these women over time.…”
Section: Introductionmentioning
confidence: 98%
“…The impact is usually multidimensional, affecting physical functioning, mental health, and socio-economical aspects [3,4]. So far, some studies researched long-term mental health consequences in women with MNM, such as depression and quality of life (QoL), but results are inconclusive [5][6][7][8][9][10][11][12][13]. For instance, most studies (e.g., conducted in Morocco [7], Benin [8], and Burkina Faso [9]) found that women with MNM had an increased risk of developing depression in the post-partum year, especially if they had lost their baby.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quantitative results of the current study, although showing negative impacts on maternal functioning, sexual health and quality of life, [29][30][31] were not able to identify an important impact on the occurrence of PTSD among women experiencing SMM at least up to 5 years after the event. 32 3-The woman in a vulnerable state and the challenges of daily practice in health care facilities:…”
Section: Resultsmentioning
confidence: 99%
“…In women who experience a severe pregnancy‐related complication, psychological morbidity may be even more prevalent and its impact may be profound. Mental disorders including depression, anxiety, and post‐traumatic stress disorder (PTSD) can emerge and remain long after childbirth, and this can potentially lead women to use drugs in the postpartum period …”
Section: Introductionmentioning
confidence: 99%
“…Mental disorders including depression, anxiety, and posttraumatic stress disorder (PTSD) can emerge and remain long after childbirth, and this can potentially lead women to use drugs in the postpartum period. 3,9,10 Qualitative studies of women who suffered a maternal near miss (organ failure but survival of a severe clinical event) show that they felt helpless and afraid of a potentially life-threatening event. 1 This can lead to negative feelings that may disappear over time, but may also persist for some women.…”
Section: Introductionmentioning
confidence: 99%